Virus-specific T-cells from third party or transplant donors for treatment of EBV lymphoproliferative diseases arising post hematopoietic cell or solid organ transplantation - O’Reilly, Richard J.; Prockop, Susan; Oved, Joseph H. (Frontiers in Immunology, 2024)
EBV + lymphomas constitute a significant cause of morbidity and mortality in recipients of allogeneic hematopoietic (HCT) and solid organ transplants (SOT). Phase I and II trials have shown that in HCT recipients, adoptive transfer of EBV-specific T-cells from the HCT donor can safely induce durable remissions of EBV + lymphomas including 70->90% of patients who have failed to respond to treatment with Rituximab. More recently, EBV-specific T-cells generated from allogeneic 3 rd party donors have also been shown to induce durable remission of EBV + lymphomas in Rituximab refractory HCT and SOT recipients.In this review, we compare results of phase I and II trials of 3 rd party and donor derived EBVspecific T-cells. We focus on the attributes and limitations of each product in terms of access, safety, responses achieved and durability. The limited data available regarding donor and host factors contributing to T cell persistence is also described. We examine factors contributing to treatment failures and approaches to prevent or salvage relapse. Lastly, we summarize strategies to further improve results for virus-specific immunotherapies for post-transplant EBV lymphomas.